2021
DOI: 10.3389/fimmu.2021.636618
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PTPN22 Allotypes on Innate and Adaptive Immune Function in Health and Disease

Abstract: Protein tyrosine phosphatase, non-receptor type 22 (PTPN22) regulates a panoply of leukocyte signaling pathways. A single nucleotide polymorphism (SNP) in PTPN22, rs2476601, is associated with increased risk of Type 1 Diabetes (T1D) and other autoimmune diseases. Over the past decade PTPN22 has been studied intensely in T cell receptor (TCR) and B cell receptor (BCR) signaling. However, the effect of the minor allele on PTPN22 function in TCR signaling is controversial with some reports concluding it has enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 147 publications
(426 reference statements)
1
34
0
Order By: Relevance
“…A single nucleotide polymorphism in PTPN22, rs2476601, is associated with increased risk of T1D, reduced age at onset, and reduced residual β-cell function at diagnosis. It affects T-cell receptor and B-cell receptor signaling as well as other adaptive and innate immune cell processes [ 83 ]. Sharp et al [ 80 ] demonstrated that single nucleotide polymorphisms in PTPN2/22 are found significantly in patients with Crohn’s disease and lead to an increase in T-cell proliferation due to loss of negative regulation, an increase of pro-inflammatory cytokines such as IFN-γ, and an increase of susceptibility to mycobacterial infections.…”
Section: Epitopes Proteins and Genes Of Nontuberculous Mycobacteria A...mentioning
confidence: 99%
“…A single nucleotide polymorphism in PTPN22, rs2476601, is associated with increased risk of T1D, reduced age at onset, and reduced residual β-cell function at diagnosis. It affects T-cell receptor and B-cell receptor signaling as well as other adaptive and innate immune cell processes [ 83 ]. Sharp et al [ 80 ] demonstrated that single nucleotide polymorphisms in PTPN2/22 are found significantly in patients with Crohn’s disease and lead to an increase in T-cell proliferation due to loss of negative regulation, an increase of pro-inflammatory cytokines such as IFN-γ, and an increase of susceptibility to mycobacterial infections.…”
Section: Epitopes Proteins and Genes Of Nontuberculous Mycobacteria A...mentioning
confidence: 99%
“…The rs2476601 variant in the coding region of the protein tyrosine phosphatase non-receptor type 22 ( PTPN22) gene is one of the most strongly associated risk variants shared across autoimmune diseases including RA, T1D, and SLE ( 37 ). PTPN22 is notable for its role across multiple immune cell types including lymphocytes, natural killer (NK) cells, neutrophils, monocytes, macrophages, and DCs ( 37 ). In T and B cells, PTPN22 regulates antigen receptor signaling ( 38 ), making it a major focus of studies investigating its role in autoimmunity risk.…”
Section: Shared Genetic Variants Across Autoimmune Diseasementioning
confidence: 99%
“…Human studies have also shown that the rs2476601 variant influences T cell maturation including increased CD4 memory T cells ( 43 ) and an increase in Th1 cells ( 44 ). In addition, this variant impacts TCR signaling, although the jury is still out as to whether it is a gain- or loss-of-function mutation, and this is likely dependent on context ( 37 ). This PTPN22 variant has also been recently implicated in cDC2 homeostasis because expression of the orthologous polymorphism in mice lead to expansion of cDC2 ( 45 ).…”
Section: Shared Genetic Variants Across Autoimmune Diseasementioning
confidence: 99%
“…The molecular consequences of the PTPN22 mutation and the impact on T1D risk have been discussed extensively before ( 92 , 93 ). The debate regarding the impact of the T1D risk variant on T cells remains as the results support both gain-of-function and loss-of-function as a mechanism ( 94 ).…”
Section: Ptpn22mentioning
confidence: 99%
“…In myeloid cells, PTPN22 is involved in the downstream signaling of TLR4, TLR7/8, NOD2 and cytokine receptors (reviewed in ( 92 )). In this case, LYP does not work as a phosphatase but promotes TRAF3 ubiquitination and TLR-induced upregulation of type I interferons (IFNs).…”
Section: Ptpn22mentioning
confidence: 99%